Authorization Recycling in Attribute-Based Access Control - An, Yan; Helil, Nurmamat (Wireless communications and mobile computing, 2023)
In most access control scenarios, the communication between the PDP (policy decision point) and the PEP (policy enforcement point) can cause high authorization overhead. Authorization recycling enables PEP to use the previous access control decisions fetched from the PDP to handle some upcoming access control requests, reduce authorization costs, and increase the efficiency of access control decision-making. Inspired by the RBAC (role-based access control) authorization recycling mechanism, this article first presents an ABAC (attribute-based access control) model based on Boolean expressions of subject and object attributes. It then proposes an authorization recycling approach for this model. In this approach, we provide construction and update methods for authorization data caches and access control decision-making rules for SDP (secondary decision point) by using the caches. The proposed approach can deduce precise and approximate access control decisions from the cache of authorization data, reducing communication between the PEP and the PDP. Finally, the feasibility of the proposed method is verified by conducting a small-scale test. ABAC, SDP, authorization recycling, and authorization caching.